Changes derived by the silvopastoral management in Nothofagus antarctica forests of Tierra del Fuego compared to other productive environments - Martínez Pastur, Guillermo José; Rosas, Yamina Micaela; Cellini, Juan Manuel; Huertas Herrera, Alejandro; Toro Manríquez, Mónica D.R.; Lencinas, María Vanessa; Benítez, Julieta; Pechar, Sebastián; Peri, Pablo Luis (Agroforestry Systems, 2024)
Silvopastoral systems (SPS) are suggested to promote a balance between productive alternatives and ecological values. The aim of this study was to determine the changes generated by SPS (thinning + livestock) in Nothofagus antarctica (ñire) forests compared to other productive environments (unmanaged forests, dry grasslands, wet grasslands). A total of 16 areas (4 treatments x 4 replicates) were selected in El Roble ranch (Tierra del Fuego, Argentina), where 50 variables were surveyed through plots (forest structure, forage, animals, biodiversity) and sampling in soil pits. Indices for each component and univariate analyses were performed to compare the studied environments. The results showed that SPS generate significant changes in the studied components, causing positive and negative synergies on the studied variables (e.g., forage biomass increases 1.5 times, p = 0.008). These changes promoted new productive environments with intermediate characteristics between forests and grasslands (dry and humid). It was observed that tree roots, unlike herbs and grasses, were located not only in the upper layer, but also appear in higher percentages at deeper layers (e.g., tree roots between 20 and 30 cm soil depth are comparable to those values found between 0 and 10 cm, p = 0.035). These results allowed us to identify the factors of change in the studied components, as well as potential indicators for monitoring. Understanding the dynamics and interactions among the different ecosystem components, allowed to generate new proposals that must be economically viable (e.g., management costs vs. growth of trees and forage) and environmentally sustainable (e.g., conservation of the original biodiversity). EEA Santa Cruz Fil: Martínez Pastur, Guillermo José. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas (CADIC); Argentina. Fil: Rosas, Yamina Micaela. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas ...